Zadania i role nauczycieli języków obcych w świetle potrzeb edukacyjnych młodzieży gimnazjalnej - Białek, Magdalena (Neofilolog, 2017)
The tasks that the contemporary teachers of foreign languages face as well as the roles that they should assume as leaders of the educational process are of complex nature. This complexity is a result of numerous social changes and transformational processes. In response to these changes, educators’ roles keep being redefined so that the tasks that the teachers take up could be as effective as possible in the given time and space. These modified roles of teachers are the subject of this article. In the theoretical part, the results of the analysis of the literature on foreign language teaching are presented, with the focus on teacher roles and tasks. The analysis indicates the main development tendencies in foreign language teaching after the breakthrough caused by the communicative approach. The empirical part presents the outcome of research into how contemporary middle school students identify the roles and tasks of the teacher of German. The results of the study may contribute to the scholarly reflection on the role of the teacher in the foreign language teaching process.